Tuning of Water Vapor Permeability in 2D Nanocarbon-Based Polypropylene Composite Membranes - Glykeria A. Visvini; Georgios N. Mathioudakis; Amaia Soto Beobide; George A. Voyiatzis (Nanomaterials)
This work focuses on the incorporation of 2D carbon nanomaterials, such as graphene oxide (GO), reduced graphene oxide (rGO) and graphene nanoplatelets (GNPs), into polypropylene (PP) via melt mixing. The addition of these 2D carbon nanostructured networks offers a novel approach to enhancing/controlling the water vapor permeable capabilities of PP composite membranes, widely used in industrial applications, such as technical (building roof membranes) or medical (surgical gowns) textiles. The study investigates how the dispersion and concentration of these graphene nanomaterials within the PP matrix influence the microstructure and water vapor permeability (WVP) performance. The WVP measurements were conducted via the “wet” cup method. The presence of either GO, rGO or GNPs in the new polyolefin composite membranes revealed 6- to 7-fold enhanced WVP values compared to pristine PP. This improvement is attributed to the nanoindentations created at the interface of the carbon nanoinclusions with the polymer matrix in the form of nanopores that facilitate water vapor diffusion. In the particular case of GO and rGO, residual oxidative groups might contribute to the WVP as well. This is the first study to compare GO, rGO and even GNP inclusions under identical conditions, providing deeper insights into the mechanisms driving the observed improvements in WVP performance.